Analysis Of Wind Pressure Effect On Gambrel Roof Of A Low-Rise Building Using Computational Fluid Dynamic (Cfd) - Suhailmi, Mardhiah Muhammad (Universiti Sains Malaysia, 2022)
Windstorms are the cause of enormous amounts of property damage, personal injury, and even death, in addition to economic loss. During windstorms, low-rise buildings, particularly those with roof structures, are at the greatest risk of being destroyed. The roof of a structure is subjected to the greatest amount of wind load when compared to the other components of a building. The results of computational fluid dynamics (CFD) simulations carried out with the objective of determining the influence of wind pressure on low-rise structures with a variety of different roof pitches. Using computational fluid dynamics (CFD) simulations, researchers have conducted a great number of experiments over the course of many years in order to analyse the wind impact. The vast majority of studies, on the other hand, were carried out by taking into account the three-dimensional environment and topography around the single-story buildings. On the other side, there are studies that use CFD simulations in a two-dimensional environment but with several kinds of roofs, such as gable roofs, flat roofs, and roof pitches of varying degrees. From the acquired data, the size and trajectories of the wind flows may be determined. Higher -Cp levels inflict a great deal more harm owing to increased suction and a wider vortex region. Variable roof pitch also has a significant impact on the airflow distribution. The presence of an overhang on a gambrel roof provides more strength than the absence of an overhang.